Growth inhibitory effect of an injectable hyaluronic acid–tyramine hydrogels incorporating human natural interferon-α and sorafenib on renal cell carcinoma cells. (1st January 2016) - Ueda, Kosuke; Akiba, Jun; Ogasawara, Sachiko; Todoroki, Keita; Nakayama, Masamichi; Sumi, Akiko; Kusano, Hironori; Sanada, Sakiko; Suekane, Shigetaka; Xu, Keming; Bae, Ki Hyun; Kurisawa, Motoichi; et al.
Graphical abstract: Abstract: Immunotherapy including interferon-alpha (IFN-α) is one of the treatment options for metastatic renal cell carcinoma (mRCC) patients. Despite clinical benefits for the selected patients, IFN-α therapy has some problems, such as poor tolerability and dose-limiting adverse effects. In addition, the frequent injections reduce a patient's quality of life and compliance. Recently, an injectable and biodegradable hydrogel system to prolong drug release is reported. In this study, we investigated the anticancer effect of IFN-α (Sumiferon®)-incorporated hyaluronic acid–tyramine (HA–Tyr) hydrogels in human RCC-xenografted in nude mice. We also evaluated the synergistic efficacy of IFN-α-incorporated HA–Tyr hydrogels + sorafenib in this model. IFN-α-incorporated HA–Tyr hydrogels + sorafenib most effectively inhibited tumor growth on human RCC cells xenografted in nude mice. In addition, IFN-α-incorporated HA–Tyr hydrogels + sorafenib inhibited the proliferation of tumor in nude mice by inducing apoptosis and the suppression of angiogenesis. Our results suggest a possibility that HA–Tyr hydrogel drug delivery system prolongs the biological half-life of natural human IFN-α and enhances its anticancer effects on human RCC cells. Statement of significance: The scope of this study is to provide an alternative approach to improve the anticancer efficacy in renal cell carcinoma (RCC) treatment by using hyaluronic acid–tyramine (HA–Tyr) hydrogel drug delivery system. We investigated the anticancer effect of natural interferon-α (IFN-α)-incorporated HA–Tyr hydrogels in RCC cells. We also evaluated the synergistic efficacy of natural human IFN-α-incorporated HA–Tyr hydrogels + sorafenib. We demonstrated that HA–Tyr hydrogel system is able to release natural human IFN-α in sustained manner and enhances its anticancer effects on human RCC cells. In addition, we suggested that IFN-α-incorporated HA–Tyr hydrogels + sorafenib exhibited most effectively anticancer effects. Hence, we believe that this approach could be applied to treatment with RCC in the future.